An Outline of the Statistics of the Polish Press 1864–1918 - Kolasa, Władysław Marek (Rocznik Historii Prasy Polskiej, 2016)
This article presents a concise description of the development of the Polish press in the years 1864-1918. The main focus of the work is on the quantitative growth and territorial distribution of the press. The study shows that over 5,886 Polish titles were being published in the years 1864-1918. The largest number of newspapers appeared in Galicia (2,323), a slightly lower number in the Russian Partition (2,018), and the lowest amount in the Prussian Partition (613); what’s more, around 371 titles were being issued on the territories belonging to the partitioning powers, and 561 titles by émigrés. Zarys statystyki prasy polskiej 1864-1918 Artykuł zawiera zwięzłą charakterystykę rozwoju oraz prasy polskiej w latach 1864-1918. Celem opracowania jest określenie jej ilościowego wzrostu oraz terytorialnego rozmieszczenia. W wyniku badań ustalono, że w latach 1864-1918 ukazało się aż 5886 tytułów drukowanych w języku polskim. Najwięcej pism ukazywało się w Galicji (2323), nieco mniej w zaborze rosyjskim (2018), zaś najmniej w prowincji pruskiej (613); ponadto 371 tytułów drukowano w głębi państw zaborczych oraz 561 na emigracji